North Atlantic Regional Water Resources Study. Appendix K. Navigation. - CORPS OF ENGINEERS NEW YORK NORTH ATLANTIC DIV (1972)
Appendix K includes estimates of the range of future waterborne commerce, in terms of total tonnage, in short (2,000 lb.) tons, for the bench mark years 1980, 2000 and 2020, and presents potential development programs and order-of-magnitude costs. The range projected for waterborne commerce is broader in the more distant future as the degree of possible error increases. The limits are such that the range includes projections for Environmental Quality, Regional Development and National Income objectives. Recreational boating is covered through a dissertation on the estimated total craft and total registered craft for the same bench mark years; with an evaluation of the extent of development required to accommodate these craft. An examination of the condition, adequacy and limitations of the waterways and major port facilities; an assessment of present and future navigation technology, and an analysis of the major trends of waterborne commodities must all be completed before undertaking a discussion of the future activity on and development of the water and related land resources of the North Atlantic Region. Appendix K to report dated Jun 72, AD-A036 616. See also Appendix L, AD-A036 624.